The Fundamental Need for Sleep in Neurocritical Care Units: Time for a Paradigm Shift - Kishore, Kislay; Cusimano, Michael D. (Frontiers in Neurology, 2021)
Intensive neurological assessments in neurocritical care settings for unduly prolonged period results in profound sleep deprivation in those patients which confounds the true neurological status of these patients, and the mounting apprehension in providers can beget a vicious cycle of even more intensive neurological assessments resulting in further sleep deprivation from being constantly woken up to be "assessed". This iatrogenic state drives these patients into deep sleep stages that impact spontaneous breathing trials, weaken immunity and lead to unwarranted investigations and interventions. There is dwindling value of prolonged frequent neuro-checks beyond the initial 24-48 hours of an intracranial event. We insist that sleep must be considered on at least an equal par to other functions which are routinely assessed. We reason that therapeutic sleep must be allowed to these patients in suitable amounts especially beyond the first 36-48 hours to achieve ideal and swift recovery. This merits a paradigm shift.